2016
DOI: 10.1155/2016/5693205
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Remodeling in Equine Asthma: What Do We Know about Mediators of Inflammation in the Horse?

Abstract: Equine inflammatory airway disease (IAD) and recurrent airway obstruction (RAO) represent a spectrum of chronic inflammatory disease of the airways in horses resembling human asthma in many aspects. Therefore, both are now described as severity grades of equine asthma. Increasing evidence in horses and humans suggests that local pulmonary inflammation is influenced by systemic inflammatory processes and the other way around. Inflammation, coagulation, and fibrinolysis as well as extracellular remodeling show c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 156 publications
(134 reference statements)
1
12
0
Order By: Relevance
“…A milder form of RAO, identified as “IAD” is characterized by nasal discharge and decreased performance, but horses with IAD display no increased respiratory effort at rest. In IAD, mixed/neutrophilic and eosinophilic inflammation may be present . Similar to human asthma, RAO and IAD respond to beta‐adrenergic agonists in combination with inhaled or systemic corticosteroids …”
Section: Asthma/obstructive Airway Disease In Other Mammalian Speciesmentioning
confidence: 99%
“…A milder form of RAO, identified as “IAD” is characterized by nasal discharge and decreased performance, but horses with IAD display no increased respiratory effort at rest. In IAD, mixed/neutrophilic and eosinophilic inflammation may be present . Similar to human asthma, RAO and IAD respond to beta‐adrenergic agonists in combination with inhaled or systemic corticosteroids …”
Section: Asthma/obstructive Airway Disease In Other Mammalian Speciesmentioning
confidence: 99%
“…Reports using models of Drosophila melanogaster (Roeder et al, 2009), canines (Padrid, 1992;Zosky and Sly, 2007), felines (Norris Reinero et al, 2004), rats (Kucharewicz et al, 2008), equines (Herszberg et al, 2006), sheep (Zosky and Sly, 2007;Scheerlinck et al, 2008), guinea pigs (Canning and Chou, 2008), nonhuman primates (Coffman and Hessel, 2005), and mice (Zosky and Sly, 2007;Nials and Uddin, 2008;Chapman et al, 2014;Aun et al, 2017) can be found in the literature. Although felines and equines spontaneously display asthma-like symptoms, 1% of cats develop eosinophilic bronchitis (Padrid, 2000;Aun et al, 2017), and horses develop heaves resulting from moldy hay (Barton and Gehlen, 2016); they are not financially viable models for asthma research. Despite the physiologic compatibility of cats and horses, as well as guinea pigs, and nonhuman primates compared with mice, the diminished feasibility based on costs, transgenic resources, and other factors has made mice the gold standard for models of asthma (Zosky and Sly, 2007;Nials and Uddin, 2008;Chapman et al, 2014;Aun et al, 2017).…”
Section: Preclinical Models Of Asthmamentioning
confidence: 99%
“…According to Barton & Gehlen (2016), disorders of the respiratory system are the most frequently diagnosed conditions in sport horses evaluated for poor performance, particularly in the lower airways such as equine recurrent airway obstruction (RAO) and inflammatory airway disease (IAD).…”
Section: Introductionmentioning
confidence: 99%
“…Since the use of fiber-optic endoscopy was first described in horses, cytological and microbiological evaluation of BALF have become the pillars in the diagnosis of respiratory disease alongside clinical and functional examinations (Barton & Gehlen 2016). Although severely asthmatic horses often show easily visible clinical signs of disease, difficulties may arise in clinical practice due to the fact that patients may be presented in remission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation